Successful treatment with venetoclax and azacitidine for extramedullary relapse of acute myeloid leukemia after cord blood transplantation - Takeda, Takaaki; Suzuki, Taisei; Enaka, Makiko; Izumi, Akihiko; Tachibana, Takayoshi; Tanaka, Masatsugu; Fujimaki, Katsumichi; Nakajima, Hideaki (Rinshō ketsueki, 2024)
A 33-year-old man was diagnosed with acute myeloid leukemia (AML). He was treated with daunorubicin and cytarabine and achieved complete remission. He underwent consolidation therapy with three cycles of venetoclax and azacitidine (VEN+AZA). He received cord blood transplantation following a reduced-intensity conditioning (RIC) regimen. After 19 months, an extramedullary mass appeared in the paranasal sinuses along with vision loss, and relapsed AML was diagnosed based on a biopsy. Palliative irradiation was performed because the patient did not wish to receive a second transplantation. A painful extramedullary mass was found in the inguinal area, and radiation therapy was performed. Subsequently, extramedullary masses appeared in the submandibular region, but radiation therapy was not feasible because the irradiation field overlapped with that of the previous therapy. The extramedullary masses decreased after two cycles of VEN+AZA therapy. This is a rare report of VEN+AZA therapy for an extramedullary relapse of AML.